AQUATIC IN ASIAN GAMES: CONTEXT OF PISA-LIKE MATHEMATICS PROBLEM - Levana Maharani; Ratu Ilma Indra Putri; Yusuf Hartono (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2019)
This study aimed to create mathematical problems of uncertainty and data contents in PISA using aquatic context that were valid, practical and had the potential effect. This study was design research of development study. The subjects in this study were 10th-grade students of Indo Global Mandiri senior high school in Palembang consisting of 20 students. Data were gathered through interviews, observation, and tests. The results of data analysis showed that there were eight valid and practical items of PISA type of uncertainty and data contents. The contents obtained using bicycles and aquatic contexts in Asian Games. The 11 out of 20 students showed reasoning skills and reasonable arguments, and 9 out of 20 students showed reasoning skills and discussions but incomplete. It was because they were not used to solving PISA type problems in learning.